The Aims of Islamic Education and the Mental Health Crisis Among the Younger Generation: A Revitalization Agenda in the Digital Era - Ahmad Shiddiq; Ade Irma Manurung; Azizah Hanum OK (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2026)
The advancement of digital technology has brought various conveniences to human life. However, it has simultaneously given rise to psychological and spiritual issues, particularly among the younger generation. The mental health crisis experienced by young people is increasingly becoming a matter of concern within the educational sphere. Various pressures—such as academic demands, the influence of social media, shifting social environments, and the erosion of spiritual values—contribute to rising stress, anxiety, identity crises, and diminished mental resilience. These conditions indicate that education should not merely focus on academic achievement but must also address character building, as well as the mental and spiritual well-being of students. This study aims to analyze the relevance of spirituality in Islamic education as a solution to the mental health crisis facing the digital generation. It examines Islamic educational thought emphasizing adab (proper conduct/etiquette), purification of the soul, the educator as a role model, and a transcendental orientation to cultivate individuals of noble character. Character education is implemented to enhance the quality of educational outcomes by fostering good personality traits in alignment with graduate competency standards. This study employs a qualitative approach, specifically library research, utilizing books, research journals, and supporting articles. The findings demonstrate that educational spirituality plays a strategic role in establishing an intellectual, emotional, and spiritual balance among students. Values such as adab, exemplary conduct, and transcendental awareness prove relevant in strengthening mental resilience, mitigating the negative impacts of digital culture, and fostering a deeper sense of meaning in life.